Investigating alternative raw materials and diet formulations on growth performance, lipid metabolism and gene expression in Atlantic salmon (Salmo salar L.) - Pratoomyot, Jarunan (University of Stirling, 2010)
Fish meal (FM) and fish oil (FO) have traditionally been central in aquaculture feed formulation but the finite global supply situation limiting future use along with issues of contaminant levels in these feed ingredients have become critical issues. The objectives of the present study were to investigate alternative feed ingredients as substitutes for both FM and FO in feeds for Atlantic salmon (Salmo salar) to ensure optimal growth, feed efficiency and health of the fish as well as maintaining the nutritional quality of the fish product to the human consumer, especially the levels of n-3 highly unsaturated fatty acid (HUFA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), in the flesh. The results of the present study revealed that there were no negative effects on growth performance, feed utilisation and apparent digestibility in Atlantic salmon when FO was substituted with vegetable oil (VO) but these parameters were affected when FM was replaced with alternative protein sources from plants and animals at high levels, despite dietary supplementation with crystalline amino acids and lecithin. Reduction in feed intake was a factor affecting growth retardation when FM inclusion decreased. However, replacing FM with alternative plant and animal proteins along with partial replacement of FO had no major effect on nutritional quality, particularly n-3 HUFA content of salmon tissues. Replacing Northern FO with decontaminated FO or blends of southern hemisphere FO and VOs strategies to reduce POP contaminants and retain high nutritional values in flesh were very successful. Dietary treatments and genetic origin of fish both had effects on tissue compositions and gene expression. All fish groups (strain/family), consist of CAL, LEAN and FAT strains, fed a diet containing VO showed significant differential expression of lipid metabolism-related genes compared to fish fed a FO diet with LEAN strain appearing to adapt to VO inclusion better than FAT strain. This thesis has demonstrated dual replacement of FM ...